2015
DOI: 10.1890/15-0131.1
|View full text |Cite
|
Sign up to set email alerts
|

Do growing degree days predict phenology across butterfly species?

Abstract: Global climate change is causing shifts in phenology across multiple species. We use a geographically and temporally extensive data set of butterfly abundance across the state of Ohio to ask whether phenological change can be predicted from climatological data. Our focus is on growing degree days (GDD), a commonly used measure of thermal accumulation, as the mechanistic link between climate change and species phenology. We used simple calculations of median absolute error associated with GDD and an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 36 publications
5
120
1
Order By: Relevance
“…Recent research has suggested that growing degree days can be useful when modelling insect population dynamics because the accumulation of temperature potentially has a direct mechanistic effect on, for example, specific developmental stages that need a certain number of warm days for successful completion (Cayton et al, 2015). At Gates, timing of precipitation throughout the year was not nearly as important as the single largest event, which had the largest PIP (PIP = 0.948 and PMC = −0.530) of any climate variable.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that growing degree days can be useful when modelling insect population dynamics because the accumulation of temperature potentially has a direct mechanistic effect on, for example, specific developmental stages that need a certain number of warm days for successful completion (Cayton et al, 2015). At Gates, timing of precipitation throughout the year was not nearly as important as the single largest event, which had the largest PIP (PIP = 0.948 and PMC = −0.530) of any climate variable.…”
Section: Discussionmentioning
confidence: 99%
“…The annual accumulation of degree days has proved to be a good indicator of spring phenology among insects (Cayton et al, 2015). The GDD measure is based on the specific temperature interval in which insect development can occur.…”
Section: Experimental Designmentioning
confidence: 99%
“…Our analyses confirm these original ideas, albeit with a focus on rates of temperature increase rather than monthly mean SST. Similarly, many terrestrial species respond to growing degree days, which is the integral of temperature over time, and is a stronger predictor of butterfly emergence than calendar date [41].…”
Section: (B) Proximate Cuesmentioning
confidence: 99%